Antioxidant properties of chromium and zinc - In vivo effects on digestibility, lipid peroxidation, antioxidant vitamins, and some minerals under a low ambient temperature - Onderci, M; Şahin, Nurhan; Şahin, Kazım; Kilic, N (Springernature, 2003)
The effects of chromium (chromium picolinate, CrPic) and zinc (ZnSO4H2O) supplementation on serum concentrations of malondialdehyde (MDA) (an indicator of lipid peroxidation) and serum status of some antioxiclant vitamins and minerals of laying hens (Hy-Line) reared at a low ambient temperature (6.8degreesC) were evaluated. One hundred twenty laying hens (Hy-Line; 32 wk old) were divided into 4 groups, 30 hens per group. The hens were fed either a basal diet or the basal diet supplemented with either 0.4 mg Cr/kg of diet, 30 mg Zn/kg of diet, or 0.4 mg Cr plus 30 mg Zn/kg of diet. Digestibility of nutrients (dry matter [DM], organic matter [OM], crude protein [CP], and ether extract [EE]) increased by supplementation of chromium and zinc (p < 0.05). Supplemental chromium and zinc increased serum vitamins C and E but decreased MDA concentrations (p < 0.05). Additionally, supplemental chromium and zinc caused an increase in the serum concentrations of Fe, Zn, Mn, and Cr (p < 0.05). The present study showed that low ambient temperature causes detrimental effects on the digestibility of nutrients and antioxiclant status and that such detrimental effects caused by low ambient temperature can be alleviated by chromium and zinc supplementation, particularly when Cr and Zn were simultaneously included into the diet. Data obtained in the present study suggest that such supplementation can be considered as a protective management practice in a diet of laying hens for alleviating negative effects of cold stress.
Keywords: cold stress; chromium; zinc; MDA; minerals; laying hen